Identity phenomenon: specificity and aspects of understanding - Kukusheva N. E., Sheriazdanova G. R. (Interactive science, 2018)
in the article the authors comprehend the phenomenon of identity, examining the processes of formation of a modern Kazakhstani nation and a new national identity on a civil and political basis, actualizing the unique ethnic composition of the Kazakhstani society.
Keywords: личность; национальная идентичность; индивид; социальная идентичность; идентичность; идентификация; Personality; identification; identity; individual; social identity; national identity